Posttraumatic stress disorder in disaster-exposed youth: examining diagnostic concordance and model fit using ICD-11 and DSM-5 criteria - BreAnne A. Danzi; Ellen A. Knowles; Rachel C. Bock (BMC Pediatrics)
Abstract Background Competing definitions of posttraumatic stress disorder (PTSD) have been proposed by ICD-11 and DSM-5; it is unclear which diagnostic model works best for children and adolescents. Although other studies have predicted the impact of these models by approximating the criteria using older measures, this study advances the research by comparing measures designed to assess ICD-11 and DSM-5 criteria in hurricane-exposed youth. This study evaluates ICD-11 and DSM-5 (both the standard and preschool-age) diagnostic models by identifying diagnostic rates, evaluating diagnostic concordance, investigating the predictive value of constructs associated with PTSD (demographics, disaster threat and exposure, functional impairment), and examining model fit. Method The sample was exposed to Hurricane Ian (2022), a deadly Category 5 hurricane. Parents reported on disaster exposure and their child’s PTSD symptoms (n = 152; ages 7–17) using the International Trauma Questionnaire for Children and Adolescents Caregiver Version (ITQ-CG) for ICD-11 criteria and UCLA PTSD Reaction Index for DSM-5, Parent/Caregiver Report Version (RI-5) for DSM-5 criteria. Results ICD-11 PTSD symptom criteria rates were 24% and dropped to 20% when the impairment criterion was added. PTSD symptom criteria rates were 11% (10% with impairment) for DSM-5 and 13% (12% with impairment) for DSM-5 Preschool. ICD-11 rates were higher than DSM-5 and DSM-5 Preschool rates. There was no difference between DSM-5 and DSM-5 Preschool rates of PTSD. There was moderate to substantial concordance between ICD-11 and the DSM-5 models. All diagnostic models were associated with exposure and impairment, but only ICD-11 was associated with threat. ICD-11 was the only one to evidence acceptable model fit. Conclusions Using the ITQ-CG and RI-5 to assess PTSD in youth, results showed higher PTSD diagnostic rates for ICD-11 than DSM-5; this contradicts prior findings (based off approximated ICD-11 criteria) and seems largely due to differences in symptom thresholds used by the two measures. The ITQ-CG exhibited excellent model fit and was associated with several constructs important to PTSD.